(untitled) (Journal of the College of Languages (JCL), 2019)
The paper deals with the marked vocabulary of Russian and Arabic language, and the extrapolated to the phraseological layer of the mentioned language systems. Specificity of the functioning of this process is presented against the backdrop of the peculiarities of the existence of Russian and Arabic languages. Attention is focused on the fact that linguistic markers should be considered as a kind of keys that represent the specificity of the experience of being experienced by an individual in ontological reality. It is asserted that marking can be revealed practically at all levels of the language polysystem, but it is especially productive on its lexical layer, in particular, on the basis of lexicology and phraseology. Аннотация В статье рассмотрена маркированная лексика русского и арабского языков, экстраполированная на фразеологическом слое упомянутых языковых систем. Репрезентирована специфика функционирования оного процесса на фоне особенностей бытования русского и арабского языков. Акцентировано внимание на том, что лингвистические маркеры необходимо рассматривать в качестве своего рода ключей, репрезентирующих специфику пережитого индивидуумом опыта бытования в онтологической реальности. Утверждается, что маркировка может быть выявлена практически на всех уровнях языковой полисистемы, но особенно продуктивной она является на лексическом ее слое, в частности – на базисе лексикологии и фразеологии. огии и фразеологии.